Mobile Health (mHealth) Applications for Stroke Rehabilitation: A mini review - Arshad Nawaz Malik; Ayesha Afridi; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
Mobile Health (mHealth) applications are transforming stroke rehabilitation, through personalized care and datadriven insights. These applications employ AI-driven algorithms, tele-rehabilitation, wearable technologies, and gamification to enhance recovery process. The objective of this mini review is to explore the transformative role of Mobile Health (mHealth) applications in stroke rehabilitation, highlighting its capacity to transcend geographical barriers and establish extensive support networks connecting stroke survivors, caregivers, and healthcare professionals. Particularly in developing countries like Pakistan, where healthcare resources may be limited, mHealth offers a viable solution to bridge the gap in stroke care. By facilitating access to rehabilitation services, mHealth can significantly improve outcomes for stroke survivors in these regions. This integration of mobile technology with stroke rehabilitation not only promises personalized and more effective rehabilitation but also presents a unique blend of technology and compassion. This evolution in healthcare holds the potential to redefine stroke recovery, marking a significant milestone in the journey towards more inclusive, efficient, and compassionate care solutions. Keywords: Mobile Health, mHealth applications, stroke rehabilitation, personalized interventions, and technology integration.